Normal Criteria of Function Families Related to a Result of Drasin - Zhu Bing; Lin Jianming; Yuan Wenjun (Discrete Dynamics in Nature and Society)
We study the normality of families of meromorphic functions related to a result of Drasin. We consider whether a family meromorphic functions F whose each function does not take zero is normal in D, if for every pair of functions f and g in F, f(z) and g(z) share ∞ or H(f)−1 and H(g)−1 share 0, where H(f):=f(k)(z)+ak−1f(k−1)(z)+⋯,a0f(z). Some examples show that the conditions in our results are best possible.